Organic carbon source and C/N ratio affect inorganic nitrogen profile in the biofloc-based culture media of Pacific white shrimp (Litopenaeus vannamei) - Muhammad Hanif Azhar; Eddy Supriyono; Kukuh Nirmala; Julie Ekasari (Marine Science Department Diponegoro University, 2016)
Organic carbon source and C/N ratio play an important role in aquaculture system with biofloc technology application. Nitrogen control by adding carbohydrates to the water to stimulate heterotrophic bacterial growth by converting nitrogen into bacterial biomass. The study investigated the effect molasses, tapioca, tapioca by product and rice bran as carbon sources in a biofloc media at three different C/N ratios i.e. 10, 15, and 20 on total ammonia reduction in biofloc media. Five liters of biofloc media in a conical tank was prepared for each replicate, which consisted of 500 mL of biofloc suspension collected from a shrimp culture unit with biofloc technology application and 4.5 L seawater. Pacific white shrimp culture was performed in 40L glass aquaria at a shrimp density of 30/aquarium. There was a significant interaction between carbon source and the C/N ratio applied (P<0.05). The use of molasses resulted in the highest reduction rate irrespective to the C/N ratio. Keywords: molasses, tapioca, tapioca by product, rice bran, biofloc, total ammonia nitrogen